Aprendizagem da Matemática e suas dificuldades: mecanismos genético-moleculares e cognitivos subjacentes - Annelise Julio Costa (2018)
There is a consensus that mathematical learning disorder can impact ones life not only academically, but also emotional and social aspects. Despite the increasing research volume in the area, some topics still need better elucidation. Diagnostic criteria are still controversial and need better definition. Also, some subjects, such as the disorders genetic bases, are little explored. In this way, the present thesis investigated the role of intelligence in the discrimination of children groups with and without difficulties on mathematics learning. Besides, the aim was to examine the association between genetic-molecular aspects of the dopaminergic pathway (COMT and DAT1 genes) and cognitive mechanisms (working memory and math anxiety) underlying mathematics learning. The thesis is composed of three studies. The first paper discusses the discrepancy criterion validity in a sample of school children. Such strategy defines learning disorder based on a statistically significant difference between standardized intelligence tests and school performance. The results showed that intelligence is not relevant to discriminate children groups with and without mathematical difficulties. Also, the intellectual levels impacted global cognitive measures only, having no influence on numerical abilities. Although intelligence is important in childrens profiles characterization, the study revealed the fragility of the discrepancy criterion. The last two studies showed evidence of a relationship between genetic-molecular aspects and cognitive mechanisms involved in dyscalculia. Both investigations were performed with genes that act in the dopaminergic pathways. The first investigated the association of COMT and DAT1 genes with working memory tasks performance and arithmetic school achievement. Dominance, co-dominance, and heterosis models were analyzed for the COMT and DAT1 genes individually as well as in an associative model. No main effects were found. However, interactions between gene, working memory tasks performance, and gender were identified. Regarding COMT (rs4680), a valine dominant model was considered the best for females, while for boys, the codominance model explained the cognitive measures better. For the DAT1-3'-UTR VNTR gene, a single effect was observed in the 9 repeats allele dominant model. Finally, the latter study examined differences between COMT val158met polymorphism groups in math anxiety levels and arithmetic achievement in children aged 7 to 12 years, also considering sex influences. A major effect of sex was found towards higher levels of anxiety in girls. In addition, an interaction effect indicated that homozygous boys for valine had the lowest levels of math anxiety while girls of the same genotype had the highest levels. The results of the second and third studies suggest that different genetic variations involved in dopamine bioavailability are associated with measures that directly influence mathematics learning, and also that this relation is sex-dependent. The present thesis shows the complexity of the mathematics learning investigation on cognitive neurosciences field. The detailed understanding of childrens with dyscalculia suspicion cognitive profiles is relevant for diagnosis and also for the orientation of intervention strategies. The study of genetic aspects of numerical cognition is still exploratory. However, there is a direction for future investigations to better understand dyscalculia and thus intervene in the promotion of learning and life quality of children with this disorder.